1973
DOI: 10.1037/h0034519
|View full text |Cite
|
Sign up to set email alerts
|

Who's afraid of death?

Abstract: The study focused on selecting major demographic variables (including personal nearness to death and recent experience with death) significantly related to fear of personal death. Use was made of a multilevel criterion to study 371 persons, encompassing physically ill and emotionally disturbed patients and healthy individuals. Age and religious self-rating were the only two predictor variables found to be consistently associated with personal fear. The configurational profile emerging from analysis of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
6

Year Published

1979
1979
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 13 publications
6
76
0
6
Order By: Relevance
“…The particular (MFODS) fears of death that were correlated with maternal grief were fear of the unknown, fear of premature death, and fear of conscious death. These findings echo those of Feifel and Branscomb (1973) who reported that consciously experienced fear of death was described in terms of fear of the unknown and fear of premature death. Similarly, Florian and Mikulincer (1997) showed that university students who had recently experienced a ''significant other'' bereavement compared with those not recently bereaved exhibited more fear related to the ''unknown nature of death'' and ''loss of self-fulfillment''.…”
Section: Discussionsupporting
confidence: 88%
“…The particular (MFODS) fears of death that were correlated with maternal grief were fear of the unknown, fear of premature death, and fear of conscious death. These findings echo those of Feifel and Branscomb (1973) who reported that consciously experienced fear of death was described in terms of fear of the unknown and fear of premature death. Similarly, Florian and Mikulincer (1997) showed that university students who had recently experienced a ''significant other'' bereavement compared with those not recently bereaved exhibited more fear related to the ''unknown nature of death'' and ''loss of self-fulfillment''.…”
Section: Discussionsupporting
confidence: 88%
“…Gender, religious commitment, and age, for example, have often been examined in the context of death-related fear. Acknowledgement of concern about death is now widely recognized in the psychological literature, with fear of death being the central tenet (Cicirelli, 1999;Conte, Plutchik & Weiner, 1992;Feifel & Branscomb, 1973;Kastenbaum & Aisenberg, 1972;Kastenbaum & Costa, 1977;Feifel, 1969;Feifel & Hermann, 1973;Feifel & Nagy, 1981;Hinton, 1967;McCarthy, 1980;Stringfellow, 1963;Swenson, 1961;Templer, 1971). But what is it about death that makes people react with fear?…”
Section: Why Do We Fear Death?mentioning
confidence: 99%
“…For instance, contrary to the earlier notion that religion helps individual to cope with death anxiety, Feifel's [39] research showed that religiosity was negatively correlated with death and anxiety towards death. In yet another study subsequently, Feifel et al [40] found a negative association between religiosity and death anxiety.…”
Section: Religion and Attitude/belief Towards Deathmentioning
confidence: 93%